Occupational exposures and cancer: a review of agents and relative risk estimates. Issue 8 (7th May 2018) - Marant Micallef, Claire; Shield, Kevin David; Baldi, Isabelle; Charbotel, Barbara; Fervers, Béatrice; Gilg Soit Ilg, Anabelle; Guénel, Pascal; Olsson, Ann; Rushton, Lesley; Hutchings, Sally J; Straif, Kurt; Soerjomataram, Isabelle
Abstract : Objectives: The contribution of occupational exposures to the cancer burden can be estimated using population-attributable fractions, which is of great importance for policy making. This paper reviews occupational carcinogens, and presents the most relevant risk relations to cancer in high-income countries using France as an example, to provide a framework for national estimation of cancer burden attributable to occupational exposure. Methods: Occupational exposures that should be included in cancer burden studies were evaluated using multiple criteria: classified as carcinogenic or probably carcinogenic by the International Agency for Research on Cancer (IARC) Monographs volumes 1–114, being a primary occupational exposure, historical and current presence of the exposure in France and the availability of exposure and risk relation data. Relative risk estimates were obtained from published systematic reviews and from the IARC Monographs. Results: Of the 118 group 1 and 75 group 2A carcinogens, 37 exposures and 73 exposure-cancer site pairs were relevant. Lung cancer was associated with the most occupational carcinogenic exposures (namely, 18), followed by bladder cancer and non-Hodgkin's lymphoma. Ionising radiation was associated with the highest number of cancer sites (namely, 20), followed by asbestos and working in the rubber manufacturing industry. Asbestos, bis(chloromethyl)ether, nickel and wood dust had the strongest effect on cancer, with relative risks above 5. Conclusions: A large number of occupational exposures continues to impact the burden of cancer in high-income countries such as France. Information on types of exposures, affected jobs, industries and cancer sites affected is key for prioritising policy and prevention initiatives.